If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (26 + -1y) * 2 + -1y * 2 = 104 Reorder the terms for easier multiplication: 2(26 + -1y) + -1y * 2 = 104 (26 * 2 + -1y * 2) + -1y * 2 = 104 (52 + -2y) + -1y * 2 = 104 Reorder the terms for easier multiplication: 52 + -2y + -1 * 2y = 104 Multiply -1 * 2 52 + -2y + -2y = 104 Combine like terms: -2y + -2y = -4y 52 + -4y = 104 Solving 52 + -4y = 104 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-52' to each side of the equation. 52 + -52 + -4y = 104 + -52 Combine like terms: 52 + -52 = 0 0 + -4y = 104 + -52 -4y = 104 + -52 Combine like terms: 104 + -52 = 52 -4y = 52 Divide each side by '-4'. y = -13 Simplifying y = -13
| -3(w+2)=7w+14 | | 5h-9h=-16+6h | | (-8+3i)-(7-3i)=0 | | (5x-7)=(4x+40) | | 5y+60=-40 | | (4z+9)+(9y-2)=180 | | 4x/5-1/2=x+2/5 | | (2y-7)=-x+4 | | 10(2x+4)=120 | | 2+19v=-8+15v | | 1.5x^2-6x+4.5=0 | | 46=4x+2y | | 4y-13+y+1=3x-5+15-x | | 1.5x^2-6x+4.5= | | -3q+4=-2q | | Y=-4(-3)+6 | | 2(3-x)-(2x+2)=4+3(x-7) | | 0.14x+0.7(3-3)=0.01(3x-2) | | 104+b^2=26b | | x^3+10=23 | | n-36=14 | | 6.7=9.9-0.8x | | 2+10=32 | | Y=-5x^2-10x-15 | | 13x=5x+3 | | (26-b)b=104 | | 5w=-95 | | 8t=10t+8 | | a=25-b | | 5y=8+4y | | Y+2+14=3y+2 | | 5+7x=1x/2+3 |